A case of wilson’s disease presenting with cerebellar ataxia - Hang, Tran Vu Diem (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
ABSTRACT Wilson’s disease (WD) is a rare inherited copper metabolism disorder with many clinical symptoms highlighted by hepatic and cerebral features. We present the case of a 17 - year - old female patient with generalized tonic - clonic seizures and cerebellar ataxia who presented to our hospital. The patient was initially diagnosed with encephalitis and epilepsy before being identified with WD based on clinical and laboratory data. The patient had made a significant clinical recovery after six months of follow - up.